2012
DOI: 10.1200/jco.2012.41.9416
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Maintenance Therapy After Autologous Stem-Cell Transplantation in Patients With Relapsed CD20+ Diffuse Large B-Cell Lymphoma: Final Analysis of the Collaborative Trial in Relapsed Aggressive Lymphoma

Abstract: In relapsed DLBCL, we observed no difference between the control group and the rituximab maintenance group and do not recommend rituximab after ASCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
183
1
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(207 citation statements)
references
References 31 publications
9
183
1
9
Order By: Relevance
“…19 This finding likely is a reflection of less rapid rituximab clearance in women, which in turn leads to higher blood concentrations of rituximab. This observation could suggest a benefit of rituximab post auto-HCT in females (and possibly in males using higher than standard doses of rituximab), but this question remains unsettled.…”
Section: Modification Of Salvage Therapymentioning
confidence: 91%
“…19 This finding likely is a reflection of less rapid rituximab clearance in women, which in turn leads to higher blood concentrations of rituximab. This observation could suggest a benefit of rituximab post auto-HCT in females (and possibly in males using higher than standard doses of rituximab), but this question remains unsettled.…”
Section: Modification Of Salvage Therapymentioning
confidence: 91%
“…76 This was evident only in premenopausal and not postmenopausal women, suggesting hormonal factors are involved. A recent retrospective study of 1793 DLBCL patients confirmed the adverse prognostic factor of male gender in response to RTXcontaining therapeutic regimen.…”
mentioning
confidence: 95%
“…This study may also further investigate the interesting possible difference between pre-and post-menopausal women suggested in the study of Gisselbrecht. 76 The results of these studies could induce the scientific community to switch from 6 to 8 cycles of RTX in the treatment of DLBCL. The SMARTE-R-CHOP14 study 82 will show us, instead, if it is convenient also to change the schedule of RTX administration.…”
mentioning
confidence: 99%
“…Das ereignisfreie und Gesamtüberleben konnte für die Hochrisikogruppe "Frührezidiv oder primär refraktär" leider nicht explizit ausgewiesen werden, die Ansprechrate lag jedoch deutlich niedriger als bei Spätrezidiven. In der CORAL-Studie hatten Patienten mit Früh-rezidiv ein Gesamtüberleben < 20 % [1]. Es ist wichtig, diese Gruppe genauer anzusehen, denn nach den Ergebnissen der DSHN-HL-R3-Studie ist mit einer allogenen Transplantation für diese Gruppe vermutlich ein besseres Überleben zu erzielen als mit autologer Transplantation [2].…”
unclassified